Exploring the Impact of Taxpayer Awareness, Knowledge, E-Samsat, and Tax Penalties on Motor Vehicle Tax Compliance - I Gede Made Bagus Wira Manuaba; I Ketut Jati (E-Jurnal Akuntansi, 2024)
Tax compliance by individuals indicates their readiness to fulfill their obligations and exercise their right to pay taxes accurately and on time, in accordance with tax legislation. This study aims to collect empirical evidence on the influence of tax knowledge, Electronic System for Motor Vehicle Tax Administration (e-SAMSAT), taxpayer awareness, and tax penalties on the compliance of motor vehicle taxpayers in Badung Regency. The research employed a non-probability accidental sampling method to select participants. To determine the sample size, the Slovin formula was applied, resulting in a total of 100 respondents. Data collection was conducted through a questionnaire, and the hypothesis was tested using multiple linear regression analysis in the Statistical Package for the Social Sciences (SPSS) software. The findings reveal that tax penalties, e-SAMSAT, taxpayer awareness, and tax knowledge significantly enhance motor vehicle taxpayer compliance in the Badung Regency. This underscores the importance of these factors in promoting tax compliance and suggests that interventions aimed at improving taxpayer education and awareness, coupled with the effective implementation of e-SAMSAT and judicious application of tax penalties, can foster greater compliance with motor vehicle tax obligations.